Peculiarities of the Reproductive System of Helix albescens (Gastrpoda, Pulmonata) - Leonov, S.V. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
The data on Helix albescens Rossmassler, 1839 reproductive system are provided. The presence of glands of the auxillary copulatory organ, that gathered in two tufts and one massive stylophore (dartsac) are noted. The diverticulum in Crimean specimens is shown to be permanently absent, and the flagellum is 1/2–2/3 times as long as penis. The penis has two papillae and the distinct pennial knob. These characters can be used for identification of H. albescens.